Smart contracts and the convention on the use of electronic communications in international contracts : Navigating International Trade Law in the digital age - Papadopoulos, Sylvia (University of Pretoria, 2024)
Mini Dissertation (LLM (Mercantile Law))--University of Pretoria, 2023.